The global financial crisis : genesis, policy response and road ahead - Nayak, Satyendra (Springer India, 2013)
The Financial Crisis, though originating in the US, is global and comparable with the Great Depression of the 1930s. The book takes both micro and macro view of the crisis. It examines the evolution of the global monetary system and looks at the crisis from a systemic angle. It examines the institutional changes in American capitalism and market mechanisms. The dynamics of the market and its cyclical characters are discussed. It examines the structural changes in the US economy. The role of globalization and international funds flow, their changing character and the growing interdependence among nations have been examined. At the micro level, the book discusses the subprime market and the gaps in the system that created the crisis. It deals with the supervisory structure and growing influence of the derivatives market and the synthetic products that are threatening the financial system. It also analyzes the fundamental changes in the global trading and payments patterns, which are influencing the US balance of payments and the US dollar. The secular changes in the structure of the US economy are impacting the global economy.  The work deals with the measures taken to resolve the crisis both in the US and on a global scale. The reforms necessary to avoid the recurrence of the crisis are outlined. The study aims to underline these factors and draw a perspective for the US dollar. It is also proposed to draw a scenario for a more efficient and equitable global monetary system with a role for the US dollar along with a new vehicle for international payments and finance. This would also include the reform of the global economic system and the IMF.  The special feature of the book is that it takes a holistic view of the problem. The systemic and macro issues are discussed in addition to its microanalysis.